2017
DOI: 10.2147/mder.s124098
|View full text |Cite
|
Sign up to set email alerts
|

Metered Cryospray™: a novel uniform, controlled, and consistent in vivo application of liquid nitrogen cryogenic spray

Abstract: In this article, a novel cryotherapy approach using a uniform, controlled, and consistent in vivo application of liquid nitrogen (LN2) spray as a Metered Cryospray™ (MCS) process is described. Although MCS may be used for many potential clinical applications, this paper focuses on the development that led to the controlled and consistent delivery of radial LN2 cryogen spray in order to generate a uniform circumferential effect and how the amount of MCS can be adapted to specifically ablate targeted diseases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…When the catheter is introduced into the bronchus, the device delivers liquid nitrogen to the nozzle at the distal end of the catheter, which is then sprayed onto the surface of the airway tissue, using the low-temperature characteristics of liquid nitrogen to ablate the diseased airway mucosal epithelium while preserving the basal cells and extracellular matrix, thereby promoting the rapid growth of healthy mucosal epithelium. 10,17 The literature on implementing cryotherapy for managing airway diseases is limited compared to its application in oesophageal diseases, as reported in studies. [18][19][20] Several studies 21,22 have shown that cryotherapy can regenerate oesophageal epithelial tissue without leaving any scars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the catheter is introduced into the bronchus, the device delivers liquid nitrogen to the nozzle at the distal end of the catheter, which is then sprayed onto the surface of the airway tissue, using the low-temperature characteristics of liquid nitrogen to ablate the diseased airway mucosal epithelium while preserving the basal cells and extracellular matrix, thereby promoting the rapid growth of healthy mucosal epithelium. 10,17 The literature on implementing cryotherapy for managing airway diseases is limited compared to its application in oesophageal diseases, as reported in studies. [18][19][20] Several studies 21,22 have shown that cryotherapy can regenerate oesophageal epithelial tissue without leaving any scars.…”
Section: Discussionmentioning
confidence: 99%
“…There is no definitive treatment to reverse airway deformation and mucus overproduction in COPD. In recent years, a novel spray cryotherapy (SCT) method has attracted the attention of scholars around the world, which induces the formation of ice crystals by spraying liquid nitrogen at −196°C through a probe at the end of the bronchoscope, destroying the tissue cell structure but preserving the extracellular matrix and promoting the regeneration of airway epithelium 10–12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RejuvenAir system is a cryosurgical device that delivers metered doses of medical-grade liquid nitrogen from a Dewar stored in a console to a catheter emitting a radial spray at its tip. Details of the device and procedure have been published [ 17 ] and are outlined in the supplementary material (sections 2.3 and 2.4). General anaesthesia, sedative and associated medications were administered as per institutional guidelines and routine clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…However, a novel approach is suggested by the observation that selective cellular ablation preserving extracellular structures is followed by rapid replacement with healthy tissue [ 15 , 16 ]. Flash-freezing at −196°C induces intracellular ice crystal formation, disrupting cellular structures, but sparing the extracellular matrix, facilitating epithelial regrowth [ 17 ]. The RejuvenAir system (CSA Medical, Lexington, MA, USA) consists of a console which stores liquid nitrogen, and a disposable catheter with a radial spray head inserted through the working channel of a flexible bronchoscope.…”
Section: Introductionmentioning
confidence: 99%